RELATIONSHIP AND IMPACTS OF CENTRAL SLEEP APNEA SYNDROME IN PEOPLE WITH HEART FAILURE: A BIBLIOGRAPHIC REVIEW - Franco De Almeida, Leonardo; Carlos de Oliveira Dutra, João; Vieira da Silveira Santos, Daniela; Romaneto Marques, Grazielle; Henrique Leite Guedes, Idrys; Luisa de Souza Holanda, Anna (Health and Society, 2021)
Central sleep apnea (CSA) is a disorder of the central ventilatory control of the nervous system characterized by prolonged episodes of apnea during the individual’s sleep period. One of the etiologies described by several scientific studies for this condition is congestive heart failure (CHF), a disease of big prevalence and relevance for contemporary medicine. This article, in addition to describing the significant aspects of sleep physiology to the current study, seeks to correlate the sleep process with the mechanisms involved in the pathophysiology of CSA in patients with CHF, as well as the impacts on the quality of life of these people.